Antimicrobial susceptibility of Pseudomonas aeruginosa before and after initiation of inhaled tobramycin in Bulgaria - Guergana Petrova; Tanya Strateva; Dimitrinka Miteva; Snezhina Lazova; Penka Perenovska (Journal of Infection in Developing Countries)
Introduction: In aim to achieve better infection control and possible eradication of the pathogens involved in chronic infections of patients with cystic fibrosis (CF) scientists have developed a new way to administer antimicrobials – inhalation. The first and so far the only available inhalable antimicrobial in Bulgaria is inhaled tobramycin (TOBI), introduced in 2009.We aimed to evaluate the antimicrobial susceptibility of Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients before and after initiation of TOBI in the regular treatment regimen. Methodology: We have determined the minimal inhibitory concentration (MIC) of 17 antimicrobials by the E-test (LIOFILCHEM) in sputa samples of 118 CF patients for the period of 2005–2014. The results were interpreted according to the annual Clinical and Laboratory Standards Institute guidelines. Results:  In the sputa of 70 patients a total of 102 P. aeruginosa isolates were found.  Sixty-eight out of 102 (66.7%) were susceptible to all studied antimicrobials. We divided the isolates in two chronological groups: those collected before the introduction of TOBI as a regular treatment in 2009 and those collected after 2009. A significant reduction (p < 0,001–0,02) in susceptibility for the strains after 2009 was noted towards piperacillin (100% vs 50%), ceftazidime (100% / 77.3%), cefepime (97.9% / 68.2%), amikacin (100% / 63.6%), gentamicin (95.7% / 40.9%), tobramycin (93.6% / 59.1%) and ciprofloxacin (93.6% / 45.5%). Conclusion: The introduction of inhaled tobramycin as a regular therapy for CF patients in Bulgaria lead to a significant change in antimicrobial susceptibility of CF P. aeruginosa.